Study of a mathematics web-based learning on the subject of mean, median and mode - Hakim, Rahman Nul; Andayani, Sri (AIP conference proceedings, 2024)
The purpose of this study is to investigate how student responses to learning using www.ganapatih.com. Descriptive quantitative research was employed as the research approach. There are seven positive and one negative items on the data gathering usage questionnaire. This study enlisted the participation of 47 students. In total, Students’ responses to www.ganapatih.com were generally positive (very well), with an 81.2 percent score.